(3aj GdEfJGL GdefRdj Jcef Mdhd(B..(3h(B..(3Mdhd (B/s - (3GdCThM, RjfH UGdMs ((3GdGScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 2000)
(3HYV GdTQcGJ GdfSGFjI GdCeQjcjI GdcHQi GdJj HOC fTGWgG aj GdefRd,JhRjY GdhMOGJ GdScfjI MSH ChLg GdGSJNOGe (B((3MVQ eUQ(B)(3,JhRjY GdhMOGJ GdScfjI MSH ChLg GdGSJNOGe (B((3Qja eUQ,Cge fJGFL GdMGdGJ GdeSJajOI ef eTQhY GdCSQ GdefJLI aj efWbI eOjfI fUQ,Cge fJGFL ebGHdI GdeSFhdjI Yf NOeGJ GdCSQ GdefJLIs
(3GdedGMb(B:(3U(B.439-446(3;HHdjhZQGajG(B:(3U(B.455-474s
Keywords: (3GdGbJUGO GdefRdjs